Anti-Inflammatory and Reactive Oxygen Species Suppression through Aspirin Pretreatment to Treat Hyperoxia-Induced Acute Lung Injury in NF-κB-Luciferase Inducible Transgenic Mice - Chuan-Mu Chen; Yu-Tang Tung; Chi-Hsuan Wei; Po-Ying Lee; Wei Chen (MDPI AG, 2020)
Acute lung injury (ALI), a common cause of morbidity and mortality in intensive care units, results from either direct intra-alveolar injury or indirect injury following systemic inflammation and oxidative stress. Adequate tissue oxygenation often requires additional supplemental oxygen. However, hyperoxia causes lung injury and pathological changes. Notably, preclinical data suggest that aspirin modulates numerous platelet-mediated processes involved in ALI development and resolution. Our previous study suggested that prehospital aspirin use reduced the risk of ALI in critically ill patients. This research uses an in vivo imaging system (IVIS) to investigate the mechanisms of aspirin's anti-inflammatory and antioxidant effects on hyperoxia-induced ALI in nuclear factor κB (NF-κB)-luciferase transgenic mice. To define mechanisms through which NF-κB causes disease, we developed transgenic mice that express luciferase under the control of NF-κB, enabling real-time in vivo imaging of NF-κB activity in intact animals. An NF-κB-dependent bioluminescent signal was used in transgenic mice carrying the luciferase genes to monitor the anti-inflammatory effects of aspirin. These results demonstrated that pretreatment with aspirin reduced luciferase expression, indicating that aspirin reduces NF-κB activation. In addition, aspirin reduced reactive oxygen species expression, the number of macrophages, neutrophil infiltration and lung edema compared with treatment with only hyperoxia treatment. In addition, we demonstrated that pretreatment with aspirin significantly reduced the protein levels of phosphorylated protein kinase B, NF-κB and tumor necrosis factor α in NF-κB-luciferase+/+ transgenic mice. Thus, the effects of aspirin on the anti-inflammatory response and reactive oxygen species suppressive are hypothesized to occur through the NF-κB signaling pathway. This study demonstrated that aspirin exerts a protective effect for hyperoxia-induced lung injury and thus is currently the drug conventionally used for hyperoxia-induced lung injury.